|hu|hu?a? |ne e: ?kak?n au hi |enni |emm (Europeans are those who talk with the tip of their tongue): colonialesque knowledge, attuned thinking and the bloody body of scholarship known as Bushman studies - Staphorst, Luan (Southern African Humanities, 2021)
This article argues that the field of Bushman studies, although facing many crises of definition and focus, could be meaningful beyond the borders of its problematic past. To this end, a recent literary-philosophical pedagogical study which draws on Bushman studies, specifically research on Bleek and Lloyd’s |xam archive, is critiqued, illustrating the pitfalls of an uncritical absorption of the field into broader discourses. This critique is balanced by a reading of the oral testimony of ||kabbo, one of the |xam whose voices line the archive, as offering a view of what scholarship in Bushman studies could look like—scholarship that is ordinary, complex, and attuned. This scholarship is finally compared to and contrasted with my theorisation of colonialesque knowledge—knowledge that is not colonial proper, but that still hinders truly transformative research. It is argued that if Bushman studies, and African studies more generally, could adopt ordinary, complex and attuned scholarship—in contrast to colonialesque approaches—it would be impactful and meaningful beyond its own current confines.